Critique and Development of Modernity : From Romantic Criticism to Post-modernism - Sukron Kamil (Insaniyat : Journal of Islam and Humanities, 2017)
In the East, even in the most parts of the West, modernity has been an omnipresent phenomenon. It becomes the ultimate goal of modernization.  However, modernity appears in the Western history, shortly after birth, which emphasizes the rationality of modernity has been  criticized  among  the romantic and irrational which rely more on feelings, spontaneity, and intuition, rather than sense. The next Critics regard modernity not only as a solution, but also a problem. For example, nationalism gives birth to anti-Jewish attitudes and industrialization gives birth to imperialism. The same patter goes with science and technology. It is problematic in axiology,  ontology  and  epistemology. The universality of science in the latter period is rejected trough relativity theory and quantum theory. in the view of the post-structuralist, science is considered as a product of power. Modernity is also considered to have made a person has lost  the soul and  spirituality. Regarding the development of  modernity, it is called postmodernity, for some experts, it is a new social  configuration  which is  different, even disconnected with early modernity.  As  for  the  opposite, modernity today is a continuation of the previous modernity as a reflexive project to make life goes forward.DOI: 10.15408/insaniyat.v1i2.5638